DIGITAL VILLAGE TELEVISION AS GOVERNMENT PUBLIC RELATIONS MEDIA TO DISSEMINATE INFORMATION - Farhan, Raihan; Sunuantari, Manik (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The gap in information dissemination is one of the problems that befell the people in Batu City. In 2020, the Ministry of Communication and Informatics’ service (Diskominfo) and KIM of Batu City formed 23 Digital Village Televisions named